‘The Call to Islam’ Focusing on the Role of Translation as a Method of Da`wah and its Importance towards the Spiritual Development of the Mualafs in Islam - Mat Akhir, Noor Shakirah; Abdul Rahman, Wan Rose Eliza; Hamjah, Salasiah Hanin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Translation plays an important role as a method of da`wah in Islam. Through translation there exists an extension of knowledge and ideas from one language to another and from one culture to another. The objectives of this paper are to examine the development of translation in Islam and to identify the role of translation as a method of da`wah. The result shows that translation plays an important role as a mediating activity in helping to solve the problems and challenges in the Islamic world nowadays, and as a strategy for disseminating Islamic knowledge and awareness as a faith, a legal and moral system and as a civilization. The result also indicated that translation has contributed to the activities of da`wah to the mualafs in Islam.